Cellulose/keratin–catechin nanocomposite hydrogel for wound hemostasis. Issue 38 (11th September 2018) - Sun, Zhe; Chen, Xiangyu; Ma, Xiaomin; Cui, Xinxing; Yi, Zeng; Li, Xudong
Abstract : Rapid wound hemostatic was achieved by a composite hydrogel based on human hair keratin–catechin nanoparticles and cellulose. Abstract : Uncontrolled bleeding can lead to serious injury or even death, which often happens in some emergency situations. In previous studies, keratin was found to have a good hemostatic effect. However, the hemostatic use of pure keratin materials is limited due to keratin's poor physical properties. In the present study, a hemostatic hydrogel was prepared by adding keratin–catechin nanoparticles (KE-NPs) into cellulose hydrogel. Keratin extracted from human hair was firstly combined with EGCG, the primary constituent of catechins, to induce the self-assembly of nanoparticles. The prepared KE-NPs had a spherical shape with a particle size of around 40 nm. KE-NPs were subsequently added into cellulose hydrogel, giving rise to the cellulose/keratin–catechin composite hydrogel (KEC). The resultant KEC exhibited good adhesiveness and hemadsorption, and resulted in rapid blood coagulation. In the rat liver puncture model and the tail amputation model, KEC significantly reduced the amount of bleeding and the bleeding time. The results indicated that KEC could quickly adhere to the wound and accelerate blood coagulation. This KEC exhibited the capability of preventing blood loss and can serve as a novel type of hemostatic material.